Effects of composition and transportation logistics on environmental, energy and cost metrics for the production of alternative cementitious binders. (1st June 2018) - Nguyen, Long; Moseson, Alexander J.; Farnam, Yaghoob; Spatari, Sabrina
Abstract: The production of cement, the primary ingredient in concrete, is responsible for 5–10% of anthropogenic GHG emissions. Numerous studies have investigated ordinary portland cement (OPC) alternatives with the goal of reducing GHG emissions. This life cycle assessment (LCA) adds transportation as a focus of the assessment, in addition to the process steps from cradle to the gate of finished cementitious product. GHG emissions and cost are assessed for five cement types with comparable performance (1) OPC; (2) blended OPC with slag (SC); (3) blended OPC with fly ash (FAC); (4) metakaolin-based geopolymer (MKG); and (5) high volume limestone alkali-activated slag cements (HLAASCs). Transportation logistics are known to be critical for the cement industry, and this holds true for alternative cements. The influence of feedstock source location and transport mode within the supply chain significantly affect both environmental impacts (up to 80% of GHG emissions) and production cost (up to 65%), and should thus be a major consideration. All OPC alternatives reduce GHG emissions, even at the least beneficial points of their ranges. HLAASC reduces GHG emissions and energy consumption in all cases studied, by up to 95% and 83%. SC and FAC have comparable reductions in GHG emissions and energy, and their ranges overlap. MKG reduces GHG emissions but not energy input for the cases studied, however the energy demand may be closer to the other binders studied where the mineral is available and from low grade sources. Highlights: Feedstock acquisition, mineral processing and transportation govern environmental impact. Variability in feedstock transport distance and mode greatly affects the environmental impact and cost of cements. MKG is costly to produce in the U.S. due to limited resources. Otherwise, MKG could be competitive with OPC. HLAASCs can reduce GHG emissions by up to 95%, energy by up to 83%, and cost by up to 34% compared to OPC.